Analisis Pendapatan Usahatani Padi di Kelompok Tani Cibaregbeg Desa Cimenteng Kecamatan Curugkembar Kabupaten Sukabumi - ulpah, widia (Journal of Agribusiness, Social and Economic, 2025)
The objective of this study was to ascertain the income potential and viability of paddy rice farming within the Cibaregbeg farmer group in Cimenteng Village, Curugkembar District, Sukabumi Regency. The sampling method employed in this study was the saturated sampling method or census, whereby all members of the farmer group (n=25) were invited to participate as respondents. This study employs a survey methodology. The data analysis employed in this research is descriptive quantitative. The findings of this study indicate that the average revenue received by farmers who are members of the Cibaregbeg farmer group is Rp18,872,000 per hectare per growing season, with a total cost of Rp9,609,208 per hectare per growing season, resulting in a total income of Rp9,374,720 per hectare per growing season. The results of the R/C ratio analysis indicated a ratio of 1.98, which signifies that for every 1 rupiah spent on rice paddies in the Cibaregbeg farmer group, a revenue of 1.98 is generated. These findings substantiate the feasibility of rice paddies cultivation in the Cibaregbeg farmer group.